Emotional Responses to Social Media Experiences Among Adolescents: Longitudinal Associations with Depressive Symptoms. Issue 6 (2nd November 2022) - Nesi, Jacqueline; Rothenberg, W. Andrew; Bettis, Alexandra H.; Massing-Schaffer, Maya; Fox, Kara A.; Telzer, Eva H.; Lindquist, Kristen A.; Prinstein, Mitchell J.
ABSTRACT: Objective: The degree to which adolescent social media use is associated with depressive symptoms has been the source of considerable debate. Prior studies have been limited by a reliance on cross-sectional data and measures of overall "screen time." This study examines prospective associations between adolescents' emotional responses to social media experiences and depressive symptoms, and examines gender differences in these processes. Method: A school-based sample of 687 adolescents (48.6% girls; Mage = 14.3; 38.1% White, 29.4% Hispanic, 23.0% Black) completed measures of positive and negative emotional responses to social media experiences and depressive symptoms at two time points, one year apart. Results: Higher levels of depressive symptoms were associated with more frequent negative emotional responses to social media experiences one year later, whereas greater positive emotional responses to social media were associated with later depressive symptoms. Girls reported overall greater emotional responses to social media experiences, but gender did not moderate associations between these emotional responses and depressive symptoms. Conclusion: Findings highlight the importance of examining adolescents' positive and negative emotional experiences in the context of social media use, and the ways in which these experiences intersect with depressive symptoms, so as to identify youth who may be most vulnerable to negative effects of social media use.